Informal economy and police control in public spaces: the case of the car washers in the city of Santa Rosa (Huellas, 2016)
The article has as main objective to analyze how power relations are built relative to the differential uses of public space in the city of Santa Rosa, based on the intervention of young people known by the public opinion as ‘trapitos’ or car washers.Thus, the article identifies the practices through which workers appropriate their "territories", the control mechanisms imposed by the police (as a constituent part of the State), and the representations about  trapitos constructed by the mass media that reflect conceptions rooted in broad sectors of society.The work is inscribed in the philosophical trend that understands space as an expression of power relations and incorporates the concepts of territory and territoriality to account for these relationships.
Keywords: Informal economy; public space; power relationships; control mechanisms.